ANALISIS DISIPLIN KERJA KARYAWAN PADA PT. PESONA PUTRA PERKASA CABANG PAMULANG KOTA TANGERANG SELATAN - Dita Murni Gulo; M. Anton Nurhidayat (Journal of Research and Publication Innovation, 2025)
The purpose of this study is to determine the analysis of employee work discipline at PT. Pesona Putra Perkasa Pamulang branch, South Tangerang city. This study is a study that uses a qualitative approach with a phenomenological model. Based on the results and analysis of the research that has been done, the author that. Work discipline at PT. Pesona Putra Perkasa is running well. However, under certain conditions, the company still provides tolerance as a form of empathy for employee personal obstacles. The implemented supervisory system, both through attendance and superior monitoring, helps maintain discipline. The application of sanctions and rewards is also carried out fairly to encourage compliance and work motivation.